The role of dermoscopy in the diagnosis of acral melanocytic nevi - Woźniak, Wioletta; Wawrzynkiewicz, Magdalena; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2012)
Dermoscopy is a non-invasive diagnostic technique linking clinical dermatology and dermatopathology by enabling the visualization of morphological features of the skin not seen by the naked eye. The most important role of dermoscopy is to differentiate malignant melanoma from other pigmented lesions, particularly early melanoma from benign melanocytic nevi. The dermoscopic diagnosis of pigmented skin lesions is based on various analytic approaches or algorithms that have been set forth in the last few years, such as pattern analysis, the ABCD rule, the 7-point checklist, the three-point checklist, and the Menzies scoring method. The anatomical structure of acral volar skin determines unique dermoscopic features of pigmented lesions located in this anatomical site. The knowledge of specific dermoscopic patterns of nevi and melanomas located on the palms and soles can increase diagnostic accuracy of pigmented acral melanocytic skin lesions. There is a significant correlation between dermoscopic structure and dermatopathological findings. In recent years, several studies have reported various dermoscopic patterns of benign and malignant melanocytic volar skin lesions. Parallel furrow, lattice-like, fibrillar pattern for benign lesions and parallel ridge and diffuse pigmentation pattern for malignant changes were defined. Early detection and diagnosis of malignant melanoma on acral skin are very important to improve the prognosis. That is why it is crucial to examine acral parts of the skin during the examination of the patient.